Review of The Institutional View on The Liberalization and Management of Capital Flows : Background Note on Assessing Systemic Financial Stability Risks Due to FX Mismatches. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2022)
This note outlines the approach of the proposed revision to the Institutional View (IV) when assessing whether systemic financial stability risks are elevated due to foreign currency (FX) mismatches. The approach builds on the staff guidance regarding risk assessments in bilateral surveillance, while allowing for flexibility to draw on future advances in best practice. This note proposes a two-step approach to assess systemic risks from FX mismatches. This note is organized as follows. Section II outlines the sources of systemic risks stemming from FX debt and potential amplification channels. Section III outlines the risk assessment approach in practice and Section IV concludes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Money and Monetary Policy; Political Economy